Conquering the box office: Factors influencing success of international movies in Russia - Sophia Gaenssle; Oliver Budzinski; Daria Astakhova (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2018)
This paper empirically examines various factors influencing box office success of international movies in Russia between 2012 and 2016. Three groups of success factors are distinguished: distribution related (e.g. budget, franchise), brand and star effects (e.g. top actors or directors), and information sources (e.g. critics and audience rating). We extend the literature by applying novel concepts such as Google-hits as indicator for electronic word of mouth. Moreover, we add novel region-specific variables like seasonality, time span between the world and local release, attendance of international stars at Russian movie premieres and title adaptation into the Russian language. The results indicate that budget, franchise, electronic word of mouth through the internet and audience ratings exert a significantly positive influence on Russian box office success. Whereas, we find no evidence of star effects in our sample and significantly negative effects for international critics, and, interestingly, the adaption of movie titles.
Keywords: L10; L82; 330; motion picture economics; movies; entertainment; box office success; Russia